Food habits of Geoffroy's cat (Leopardus geoffroyi) in the central Monte desert of Argentina - Bisceglia, Silvina Beatriz Catalina (2008)
Geoffroy's cat (Leopardus geoffroyi) is a little-known South American felid. Here we report the first detailed data on its seasonal food habits in a protected area of the central Monte desert, Argentina. We collected and analyzed 182 scats, identifying a total of 441 prey items, with 2.4±1.5 prey items per scat (range=1-10). Our results confirm that, as with most other felids, Geoffroy's cat is a small-sized predator specialized in capturing vertebrates. Small mammals were the most frequent prey items, representing at least the 63.3% of the food items in each season. The Sigmodontinae rodents Akodon molinae and Calomys musculinus were the most important prey throughout the study period, whereas birds and reptiles were consumed mainly during warmer seasons. Seasonal differences in diet composition were higher between warmer and colder seasons, suggesting that diet composition is constrained by seasonal fluctuation and disponibility of prey.